PENENTUAN NILAI PREMI ASURANSI PERTANIAN BERBASIS INDEKS SUHU PERMUKAAN MENGGUNAKAN METODE BURN ANALYSIS - ANGGRAENI, A.A DWI MARSITA; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 7 No 4 (2018)DO - 10.24843/MTK.2018.v07.i04.p221, 2018)
Temperature is an important factor in the production of agricultural commodities. For this reason, goverments needs to protect farmers in order to continue their farming. Climate-based agricultural insurance is an alternative to climate-related risk management. Insurance premium is given when the temperature index lower than the pre determined trigger index. The purpose of this study is to determine the stages and assumptions in determining the value of agricultural insurance premiums based on surface temperature index on cocoa commodities using the method of burn analysis. The temperature index was determined using the burn analysis method with the temperature as the climate parameter. Trigger values ??are determined based on long run times. In this paper, the result is that when the temperature index lower than the determined trigger value, trigger payments as much as Rp.10.931.960,40 / Ha based on trigger index as many 26.145 ° C, so amount of premium payment equals Rp 215.776.